2011
DOI: 10.1177/1045389x10393767
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Energy Absorbers for Drop-induced Shock Mitigation

Abstract: This study addresses the non-dimensional analysis of adaptive magnetorheological energy absorbers (MREAs) for drop-induced shock mitigation. The control objective to ensure that the payload mass comes to rest at the end of the available stroke of the MREA, that is, a ‘soft landing.’ The governing equation of motion of a single-degree-of-freedom system with an MREA was derived. The Bingham number was defined and its effect on the system response was examined. A comprehensive non-dimensional analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…In other words, the desired "soft landing" 23,24 cannot be achieved. In this study, the settling time is defined by the end time when the payload vibration reaches a steady state evaluated by the ratio of the acceleration response of the payload to the peak excitation acceleration.…”
Section: Shock Control Performancementioning
confidence: 99%
“…In other words, the desired "soft landing" 23,24 cannot be achieved. In this study, the settling time is defined by the end time when the payload vibration reaches a steady state evaluated by the ratio of the acceleration response of the payload to the peak excitation acceleration.…”
Section: Shock Control Performancementioning
confidence: 99%
“…e minor losses refer to the energy losses which result in pressure drops at elbows and expansions, the abrupt change of section area at the inlet and the outlet, etc. Minor losses are generally neglected in long pipe systems [20,21]. In the damper with shims added to the valve of the complex shape, and at high volumetric flow rates, due to the short length of the passages, the minor losses are significant and nonnegligible relative to viscous loss [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the damper with shims added to the valve of the complex shape, and at high volumetric flow rates, due to the short length of the passages, the minor losses are significant and nonnegligible relative to viscous loss [15]. Wereley et al indicated that for the MR damper without shims, it is necessary to take minor losses into account for predicting the damping force at high piston velocity (>1 m/s) when the MR damper is subjected to intense impacts, such as aircraft landing gear, crashworthy helicopter seat suspension systems, mine blast seat suspension systems, and gun recoil systems [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, MR dampers have been employed as vibration mitigation devices for a number of applications, such as seismic dampers [1][2][3][4][5][6][7], seat dampers [8][9][10][11], and vibration isolators [12][13][14][15][16]. More recently, MR dampers have been also applied to aerial and ground vehicles as crashworthiness devices, such as landing gear oleos [17][18][19][20], impact dampers [21][22][23][24][25][26], and energy absorbers [27][28][29].…”
Section: Introductionmentioning
confidence: 99%